Multidisciplinary care management has a positive effect on paediatric obesity and social and individual factors are associated with better outcomes. (20th September 2016) - Carriere, C.; Cabaussel, C.; Bader, C.; Barberger‐Gateau, P.; Barat, P.; Thibault, H.
Abstract: Aim: The RePPOP Aquitaine network, which was established in south‐west France to prevent and treat paediatric obesity, has developed a multidisciplinary approach based on multicomponent lifestyle interventions and family‐based actions. This study assessed the impact of its care management programme and investigated the factors associated with better outcomes. Methods: The impact of the RePPOP care management programme was assessed by changes in the body mass index (BMI) Z score, between baseline and the end‐of‐care management. We focused on 982 overweight or obese children (59.9% girls) with a mean age of 10.64 years and a range of 2.4–17.9 years. A multivariate analysis examined the independent factors associated with better outcomes. Results: At the end‐of‐care management programme, 75.5% of children had decreased their BMI Z score. Initial characteristics significantly associated with better outcomes were as follows: the age at baseline between five years and 15 years of age, playing sport at a club, being followed up by RePPOP for longer than 10 months, no parental obesity and no academic difficulties. Conclusion: This study confirmed that multidisciplinary treatment had a significant positive effect on paediatric obesity and that social and individual factors affected the efficiency of the care management.